Technical and tactical analysis of youth taekwondo performance - Casolino, E.; Chiodo, S.; Tessitore, A.; Lupo, C.; Cortis, C.; Capranica, L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Several studies focused on the psychological and physiological aspects of elite Taekwondo athletes, while little information is present regarding the technical and tactical aspects of the match (Kazemi et al., 2005, 2006). Considering that athletes start training and competing around 10 years of age, an area that needs attention is the study of youth performance. Therefore, this study aimed to analyze the technical aspects of young athletes competing in the Italian Youth (i.e., Cadetti A) Taekwondo Championships in relation to gender, age, and match outcome. Methods Sixty youth taekwondo athletes (age range: 10-12 yr) participated in the study according to their weight category (ranging from -24 kg to +59 kg). Thirty-seven matches (three 1-min rounds, with 1 minute rest in between) were recorded for further match analysis. Sixteen kicking techniques, equally divided in offensive and defensive actions, were considered. A 3 (round: first vs second vs third) x 2 (match outcome: victory vs defeat) x 2 (gender: female vs male) ANOVA for repeated measures was applied to verify differences (p<0.05) in the frequency of occurrence of the kicks with relative PLSD post-hoc. Results Regardless of gender, the offensive techniques occurred more frequently (91.5%, 14±8) than defensive ones (8.5%, 1±2) (F(1, 70) = 210.1; p<0.0001). Regarding gender, the number of techniques approached the significance (F(1, 70) = 3.93; p = 0.0531), with a higher occurrence for female (3±4) than male (2±3) athletes. Moreover, females attack more and defend less than males (p=0.0054). In relation to match outcome (F(1, 70) = 18.43; p<0.0001), the number of technique was higher for winners (3±4) than losers (2±2). Regarding the rounds (F(2, 140) = 10.07; p=0.0004), differences between offensive techniques emerged only between the first (6±4) and third (4±3) while differences between the second (5±3) and third round approached significance (p=0.064). No difference was found for the defensive techniques among the three rounds. Discussion/Conclusion The lower frequency of defensive techniques with respect to the offensive ones indicates that young taekwondo athletes did not completely develop this capability. Thus, coaches are urged to stress defensive drills during their trainings. References Kazemi M. et al. (2006). Journal of Sports Science and Medicine CSSI, 114 - 121